Enhancing Maternal Caregiving Capabilities Model to Prevent Childhood Stunting: A UNICEF-Inspired Model - Eka Mishbahatul Marah Has PhD; Ilya Krisnana PhD; Ferry Efendi PhD (SAGE Publishing, 2024)
Introduction The proportion of stunted children in Indonesia is slowly decreasing. In most families, a mother is responsible for child care. The quality of maternal caregiving capability influences the mother's ability to adopt appropriate childcare practices, which is essential to prevent childhood stunting. Objectives This study aimed to develop a model to enhance maternal caregiving capabilities in preventing childhood stunting based on the UNICEF model of care. Methods The study used an analytical observational design involving a pair of mothers and their youngest 6-23-month-old children registered at Posyandu (Community-based Integrated Health Care Center). Six hundred respondents were taken using a cluster sampling technique across seven healthcare centers in Surabaya City, East Java, Indonesia. The independent variables were child, mother, father, and household factors, then maternal caregiving capabilities. The dependent variable was the nutritional behavior to prevent childhood stunting. Data were collected using questionnaires and then analyzed using the Structural Equation Model-Partial Least Squares (SEM-PLS) test. Results The study found that maternal caregiving capabilities are influenced by child (T-stat 2.605), mother (T-stat 3,800), and household factors (T-stat 10,338). Maternal caregiving capabilities affect stunting preventive behavior in children aged 6-23 months (T-stat 2.493). Household factors were the strongest factor affecting maternal caregiving capabilities. Conclusion Enhancing maternal caregiving capabilities model can be developed using its constituents, especially perceived physical health, psychological well-being, and decision-making. Household factors, including economic level and food security, were also important. High maternal caregiving capabilities were expected to enable mothers to improve their behavior to prevent childhood stunting (6-23 months).